2015
DOI: 10.1063/1.4908158
|View full text |Cite
|
Sign up to set email alerts
|

Bulk crystal growth and electronic characterization of the 3D Dirac semimetal Na3Bi

Abstract: High quality hexagon plate-like Na3Bi crystals with large (001) plane surfaces were grown from a molten Na flux. The freshly cleaved crystals were analyzed by low temperature scanning tunneling microscopy and angle-resolved photoemission spectroscopy, allowing for the characterization of the three-dimensional (3D) Dirac semimetal (TDS) behavior and the observation of the topological surface states. Landau levels were observed, and the energy-momentum relations exhibited a linear dispersion relationship, charac… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
76
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(84 citation statements)
references
References 35 publications
6
76
2
Order By: Relevance
“…At 5 K, magnetoresistance at high fields is linear with H, and MR reaches 13% at 9 T. Hence, in the metallic regime, the magnetoresistance in the high-field range is linear, not quadratic. The linear MR at low temperatures suggests that the low-T transport is linked to the linear dispersions, as observed in surfaces of topological insulators (Bi,Sb) 2 (Se,Te) 3 21-25 and SmB 6 , 26 Dirac semimetals Cd 3 As 2 27-29 and Na 3 Bi, 30 and other 3D Dirac materials. [31][32][33] In Figs. 3(a) and 3(b), we compare the magnetoresistance at high temperatures [ Fig.…”
Section: (A)]mentioning
confidence: 93%
See 1 more Smart Citation
“…At 5 K, magnetoresistance at high fields is linear with H, and MR reaches 13% at 9 T. Hence, in the metallic regime, the magnetoresistance in the high-field range is linear, not quadratic. The linear MR at low temperatures suggests that the low-T transport is linked to the linear dispersions, as observed in surfaces of topological insulators (Bi,Sb) 2 (Se,Te) 3 21-25 and SmB 6 , 26 Dirac semimetals Cd 3 As 2 27-29 and Na 3 Bi, 30 and other 3D Dirac materials. [31][32][33] In Figs. 3(a) and 3(b), we compare the magnetoresistance at high temperatures [ Fig.…”
Section: (A)]mentioning
confidence: 93%
“…37 On the other hand, linear magnetoresistance can come from quantum effects; [38][39][40] for gapless semiconductors with a linear energy spectrum, magnetoresistance in perpendicular-to-plane magnetic fields becomes linear with magnetic fields at low temperatures. 41 In recently found topological materials, [21][22][23][24][25][26][27][28][29][30] linear magnetoresistance of this mechanism has been observed. In the present case of Ru 2 Sn 3 , since the linear dispersion of the topological surface state was observed near the Fermi level by ARPES measurements at 1 K, 16 Dirac fermions on the topological surface state may be an origin of the linear magnetoresistance at low temperatures.…”
Section: (A)]mentioning
confidence: 99%
“…In the solid state, Weyl and Dirac semimetals are described at low energies by chiral fermions that realize a chiral anomaly and host topological surface states with Fermi arcs [4,5]. TaAs was recently theoretically predicted [6,7] and experimentally identified using angle-resolved photoemission spectroscopy [8,9] (ARPES) as being a Weyl semimetal, with Na 3 Bi [10][11][12][13], Cd 3 As 2 [14][15][16][17][18][19][20], and ZrTe 5 [21] likewise identified as Dirac semimetal. Rapidly other materials in the TaAs class were also shown to be Weyl semimetals [22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…Over the last two years, numerous experimental works have confirmed that certain materials such as Na 3 Bi and Cd 3 As 2 are Dirac semimetals by directly observing Dirac cones in the bulk [22][23][24][25][26][27] and Fermi arcs on the surface 28 . Many additional works observing and elucidating transport properties [29][30][31][32][33][34][35][36][37][38] and phase transitions [39][40][41][42][43][44][45][46][47][48][49] in Dirac semimetals have appeared. Even more recently, the first Weyl semimetals were discovered experimentally [50][51][52] , with evidence for Fermi arcs 52 and the unusual transport signatures they entail [53][54][55] .…”
Section: Introductionmentioning
confidence: 99%